Psychological Stress as a Modulator of Functional Recovery Following Spinal Cord Injury - Maldonado Bouchard, Sioui; Hook, Michelle A. (Frontiers in Neurology, 2014)
There is strong evidence indicating that the social environment triggers changes to the psychological stress response and glucocorticoid receptor function. Considerable literature links the subsequent changes in stress resiliency to physical health. Here, converging evidence for the modulatory role of chronic psychological stress in the recovery process following spinal cord injury (SCI) is presented. Despite the considerable advances in spinal cord injury research, we are still unable to identify the causes of variability in patients’ recovery following injury. We propose that individuals’ past and present life experiences (in the form of stress exposure) may significantly modulate patients’ outcome post SCI. We propose a theoretical model to explain the negative impact of chronic psychological stress on physical and psychological recovery. The stress experienced in life prior to SCI and also as a result of the traumatic injury, could compromise glucocorticoid receptor sensitivity and function, and contribute to high levels of inflammation and apoptosis post SCI, decreasing the tissue remaining at the injury site and undermining recovery of function. Both stress induced glucocorticoid resistance and stress induced epigenetic changes to the glucocorticoid receptor can modulate the NF-кB regulated inflammatory pathways and the Bcl-2 regulated apoptosis pathways. This model not only contributes to the theoretical understanding of the recovery process following injury, but also provides concrete testable hypotheses for future studies.